Peguero Electrocardiographic Left Ventricular Hypertrophy Criteria and Risk of Mortality - Afify, Hesham M. A.; Waits, George S.; Ghoneum, Alia D.; Cao, Xiangkun; Li, Yabing; Soliman, Elsayed Z. (Frontiers in Cardiovascular Medicine, 2018)
Background: Peguero electrocardiographic left ventricular hypertrophy (ECG-LVH) criteria are newly developed criteria that have shown better diagnostic performance than the traditional Cornell-voltage and Sokolow-Lyon criteria. However, prediction of poor outcomes rather than detection of increased left ventricular mass have become the primary use for ECG-LVH criteria which requires investigating any new ECG-LVH criteria in terms of prediction. Aims: To examine the prognostic significance of the newly developed Peguero ECG-LVH criteria Methods: We compared the prognostic significance of Peguero ECG-LVH with Cornell-voltage and Sokolow-Lyon ECG-LVH criteria in 7,825 participants (age 59.8 +13.4years; 52.7% women) from the third National Health and Nutrition Examination Survey who were free of major intraventricular conduction defects. ECG-LVH criteria were derived from digital ECG tracings processed at a central core laboratory. Results: At baseline, ECG-LVH was detected in 11.8% by Peguero; 4.3% by Cornell voltage and in 6.4% by Sokolow-Lyon. During a median follow up of 13.8 years, 2796 all-cause mortality events occurred. In multivariable models adjusted for demographics and cardiovascular risk factors, presence of Peguero ECG-LVH was associated with increased risk of all-cause mortality (HR (95% CI): 1.29(1.16,1.44). This association was not significantly different from the associations of Cornell voltage-LVH or Sokolow-Lyon LVH with all-cause mortality (HR (95%CI): 1.32(1.12, 1.55) and 1.24 (1.07, 1.43) respectively; p-values for comparisons of these HRs with the HR of Peguero ECG-LVH 0.817 and 0.667, respectively). Similar patterns were observed with other modes of mortality such as cardiovascular, ischemic heart disease and heart failure mortalities. Conclusion: Peguero ECG-LVH is predictive of increased risk of death similar to the traditional ECG-LVH criteria.